THEORETICAL FOUNDATIONS OF ESTABLISHING NEW TECHNOLOGIES ON PERSONAL MANAGEMENT SYSTEM - Nosirov, Ilxom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
It consists in the development of scientific and practical recommendations and proposals for improving team management processes in the service sector.